Changes in subjective acoustical indicators in halls with long and short reverberation times - Stauskis, Vytautas J. (Journal of Civil Engineering and Management, 2004)
Investigations of acoustics of halls of different types and volumes have disclosed good or acceptable values of the music sound clarity index C80, while the reverberation times of these halls were found to be either very short or very long. Subjectively, the acoustics of these halls are considered to be unsatisfactory. For example, the reverberation time measured in the hall of the Vilnius Opera and Ballet Theatre is about 1 s, while the values of the C"n index are either good or acceptable. A church the volume of which is 22 650 m3 has acceptable C80 values both in the performers's places and in the front rows. Similar results were obtained in other halls too.First Published Online: 14 Oct 2010